Respuesta :

Answer:

Graph (a)

Step-by-step explanation:

Given

[tex]y = \sqrt[3]{x+ 6} -3[/tex]

Required

The graph

First, calculate y, when x = 0

[tex]y = \sqrt[3]{0+ 6} -3[/tex]

[tex]y = \sqrt[3]{6} -3[/tex]

[tex]y = -1.183[/tex]

The above value of y implies that the graph is below the origin when x = 0. Hence, (c) and (d) are incorrect because they are above the origin

Also, only the first graph passes through point (0,-1.183). Hence, graph (a) is correct

Answer:

the answer is A

Step-by-step explanation:

Ver imagen fishy089